Use of Artificial Stomach−Duodenum Model for Investigation of Dosing Fluid Effect on Clinical Trial Variability - Polster, Christopher S; Atassi, Faraj; Wu, Sy-Juen; Sperry, David C (Molecular pharmaceutics, 2010)
Lilly Compound X (LCX) is an oncology drug that was tested in a phase I clinical study using starch blend capsules. The drug was given to a small patient population (4 patients) and showed large inter- and intra-patient variability. In order to evaluate the possible effect of stomach pH on exposure and ways to mitigate the variability issue, artificial stomach−duodenum (ASD) experiments were conducted to investigate the hypothesis that carefully selected dosing fluids would have an impact in minimizing exposure variability caused by the formulation, which could lead to more consistent evaluation of drug absorption in patients. The ASD data corroborates the observed variability, and was a good tool to investigate the effect of stomach pH and potential dosing solutions on duodenal concentrations. Administering capsules co-formulated with Captisol (10% drug load) along with Sprite was shown by the ASD to be an effective way to increase duodenal concentrations as well as to reduce the difference between duodenal concentrations for different gastric pH. The reduction in variability of duodenum AUC (in ASD) is expected to correlate well with a reduction of variability in patient exposure. The dosing regimen of Sprite/Captisol is therefore suggested for future clinical trials involving LCX. Furthermore, for design of early phase clinical trials, ASD technology can be used to assist in choosing the proper dosing solution to mitigate absorption and exposure variability issues.